Hubungan Pola Minum Kopi Dengan Kadar Asam Urat Darah Pada Masyarakat Di Dusun Temenggungan Desa Tawing Kecamatan Gondang Kabupaten Tulungagung - dwi wulandari, lusiana; Yuliastuti, Wiwid; Biedasari, Biedasari; Sukanto, Sukanto (Universitas Muhammadiyah Sidaorjo, 2024)
Gout is a disease caused by an inflammatory process as a clinical manifestation of the deposition of urate monosodium crystals, which accumulate in the joints due to high blood uric acid levels. In gout, it will cause a monoarticular attack characterized by severe joint pain due to acute arthritis. Various efforts have been made to reduce the problem of gout, one of the efforts is by consuming coffee. The polyphenol content in coffee is thought to be able to interfere with the action of xanthine oxidase to reduce uric acid levels. The purpose of this study is to determine the relationship between coffee drinking patterns and blood uric acid levels in the community of Temenggungan Hamlet, Tawing Village, Gondang Tulungagung District. The research design used is descriptive analysis with a cross-sectional approach. The population is the entire community of Temenggungan Hamlet, Tawing Village, a sample of 45 respondents using purposive sampling techniques. The research was carried out on March 24-31, 2018, collecting blood uric acid level data with observation sheets. Data processing and analysis were carried out using the SPSS 16.0 statistical application using the Spearman row test with α = 0.05. The results of the Spearman row statistical test showed a p-value = 0.000 < α = 0.05. So that H0 is rejected, H1 is accepted, which means that there is a relationship between coffee drinking patterns and blood uric acid levels in Temenggungan Hamlet, Tawing Village, Gondang Tulungagung. This study concludes that the pattern of drinking coffee in a day >4 grams of blood uric acid levels is within normal limits. So that coffee consumption can reduce blood uric acid levels.